2023 roadmap on photocatalytic water splitting - Detlef Bahnemann; Peter Robertson; Chuanyi Wang; Wonyong Choi; Helen Daly; Mohtaram Danish; Hugo de Lasa; Salvador Escobedo; Christopher Hardacre; Tae Hwa Jeon; Bupmo Kim; Horst Kisch; et al. (JPhys Energy, 2023)
As a consequence of the issues resulting from global climate change many nations are starting to transition to being low or net zero carbon economies. To achieve this objective practical alternative fuels are urgently required and hydrogen gas is deemed one of the most desirable substitute fuels to traditional hydrocarbons. A significant challenge, however, is obtaining hydrogen from sources with low or zero carbon footprint i.e. so called ‘green’ hydrogen. Consequently, there are a number of strands of research into processes that are practical techniques for the production of this ‘green’ hydrogen. Over the past five decades there has been a significant body of research into photocatalytic (PC)/photoelectrocatalytic processes for hydrogen production through water splitting or water reduction. There have, however been significant issues faced in terms of the practical capability of this promising technology to produce hydrogen at scale. This road map article explores a range of issues related to both PC and photoelectrocatalytic hydrogen generation ranging from basic processes, materials science through to reactor engineering and applications for biomass reforming.